Square-Stepping HIIT Combined With 'Phyllanthus amarus' Supplementation Alleviates Fasting Blood Glucose and Oxidative Stress in Overweight and Obese Individuals - Surachat Buddhisa; Nattaphol Prakobkaew; Piyapong Prasertsri; Sudarat Boonpitak; Puttipong Poncumhak; Orachorn Boonla (Physical Activity and Health)
Background: High-intensity interval training (HIIT) exercise and antioxidant supplements are an alternative to lifestyle modification for reducing oxidative stress and preventing cardiovascular risk factors; however, there remains very limited evidence regarding the potential impacts of combination of square stepping HIIT with Phyllanthus amarus (PA) on blood biochemical levels in the overweight and obese individuals. Objectives: This study aimed to investigate the effects of square-stepping HIIT combined with PA supplementation on changes in blood glucose and insulin activity, lipid profile, inflammation, and oxidative stress in overweight and obese individuals. Methods: The number of 48 overweight and obese individuals was divided into 4 groups (n = 12/group) and total 40 participants were completed the 8-week program: 1) control group (n = 8), 2) PA group (n = 12); received PA at 150 mg/day, 5 days/wk, 3) square-stepping HIIT (n = 9); received square-stepping HIIT training for 15 min/day, 3 days/wk, 8 weeks and 4) HIIT+PA group (n = 11). Venous blood was collected for measurements of the glucose, total cholesterol, triglyceride, low-density lipoprotein, high-density lipoprotein concentrations, the serum proinflammatory cytokines interleukin (IL)–6 and anti-inflammatory cytokine IL-10. Also, plasma malondialdehyde (MDA) was determined by measuring thiobarbituric acid reactive substances. Results: HIIT+PA has been a significant decrease in fasting blood glucose and oral glucose tolerance test at 120 min compared to baseline (p = 0.01). Both HIIT and HIIT+PA reduced oxidative stress by indicating a decrease in plasma MDA compared to baseline in overweight and obese individuals (p = 0.032 and p = 0.009, respectively); however, there were no significant differences between the four groups. The data on lipid profiles and inflammatory markers did not show any significant differences in all groups. Conclusion: The square-stepping HIIT combined with PA supplementation improved insulin activity and reduced fasting blood glucose and oxidative stress in overweight and obese individuals.